(untitled) (JURNAL ADMINISTRASI PUBLIK, 2016)
ABSTRACT: This research moved from the fundamental problems, namely: the extent to which employees of the Performance Role Head office Head Sario Manado city districts. Thus, this study aims: to know the effect on the Role of Employee Performance Head Head office Sario Manado city districts. This study uses a quantitative approach to the application of descriptive and explanatory. Data and information collected through a technical questionnaire distributed to 26 respondents, and equipped with observation and interview techniques (Interview), then analyzed by applying the techniques of frequency table analysis, product moment correlation and simple linear regression. Based on the analysis, it is known that: a descriptive analysis results through analysis technique table (frequency table) it is known that the distribution of respondents to variable Employee Role in the category "medium" to "low", but dominant categorized "medium" or medium with the mean average performance of 60.57%, while the Employee performance varies from moderate to high, but tends to be in the category of "moderate" with an average performance of 66.15%. Thus, it can be concluded that the role of employee positive and significant impact on performance and be contributive Head. This means that empirically Role of Employees contribute significantly and substantially to the Head of Performance, particularly the sub-district office Sario Manado city districts. Keywords: The role of employees, Head of Performance